La caza en León: ¿un sector de futuro? - González Polledo, Luis Alfonso (Estudios humanísticos. Geografía, historia y arte, 1995)
The purpose of this paper is to explore the possibilities of integration between shooting activity and rural tourism with the province of León as experimental field. Those concepts, ’hunting’ and ’rural tourism’, are not free from controversy. But his complexity overflow our concrete objectives and the paper’s size. Although we consider that first ’caution’ with rural tourism is, precisely, conceptual, we’re going to start accepting a free of trouble definition of rural tourism as the exposed in the Plan Regional de Turismo de Castilla y León, where they consider that, rural tourism, from the offer’s view, constitute a new product that include all kind of use or touristic activity taking place in the countryside.